2002
DOI: 10.1097/00004872-200206000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selective angiotensin II receptor blockade on sympathetic nerve activity in primary hypertensive subjects

Abstract: Selective ANG II receptor blockade not only decreases blood pressure, but also shifts the baroreflex set-point for the initiation of counter-regulatory reflex responses of heart rate and blood pressure towards normal blood pressure levels. Thus, data suggest that ANG II plays a pathogenetic role in the elevation of the baroreflex set point in primary hypertensive subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 31 publications
1
46
0
4
Order By: Relevance
“…On the other hand, whereas azelnidipine slightly decreased PR, amlodipine had the opposite effect. Other studies have also indicated that amlodipine's effect on PR ranged from no change to a significant increase (12,13). Eguchi et al (14) showed that amlodipine is effective at lowering BP in older hypertensives, although it may increase ventricular ectopic beats, especially when given at high dose.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, whereas azelnidipine slightly decreased PR, amlodipine had the opposite effect. Other studies have also indicated that amlodipine's effect on PR ranged from no change to a significant increase (12,13). Eguchi et al (14) showed that amlodipine is effective at lowering BP in older hypertensives, although it may increase ventricular ectopic beats, especially when given at high dose.…”
Section: Discussionmentioning
confidence: 99%
“…51 Indeed, our findings and the previously reported association between the sympathetic activation of hypertension and its cardiovascular complications 5,7,8 make it possible to argue that the choice of anti-hypertensive agents could be influenced by gender when sympathetic activation is of relevance. Some of these agents have been reported to have no effect on sympathetic activity [52][53][54][55][56] or increase it, 52,54 whereas others either curtail sympathetic activation 57 or block sympathetic effects. [54][55][56] In conclusion, hypertension in women was associated with a lower level of central sympathetic hyperactivity than in men.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 99%
“…Some of these agents have been reported to have no effect on sympathetic activity [52][53][54][55][56] or increase it, 52,54 whereas others either curtail sympathetic activation 57 or block sympathetic effects. [54][55][56] In conclusion, hypertension in women was associated with a lower level of central sympathetic hyperactivity than in men. It is suggested that this may at least partly explain the observed lower hypertension-related cardiovascular events in women than in men.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 99%
“…Amlodipine never decreases heart rate, and even increases it by activation of the baroreflex arch resulting in an increased sympathetic outflow to the vascular bed and to the heart. 10,18,19) As shown in Figure 2, Av-ME-SBP and Di-ME-SBP were both significantly reduced after cilnidipine administration. Since both the Av-ME-SBP and Di-ME-SBP were associated with future stroke events independently of each other, 6) cilnidipine seemed to be an ideal agent for controlling morning hypertension.…”
Section: Discussionmentioning
confidence: 81%